Nursing at Universidad del Valle in Cali: 65 years at the vanguard; contributions, achievements, and perspectives (Colombia Medica, 2024)
Introduction: The purpose of this paper is to depict how the Nursing School throughout its 65-year history, celebrated at the same time as Universidad del Valle does, has been at the forefront in Colombia’s southwest and Latin America, contributing to the continuous enhancement of nursing education with its undergraduate and graduate programs, as well as research and extension projects. Objective: To describe the creation and development of the nursing programs and projects in response to the contextual needs and their orientation toward innovating in nursing education.Materials and methods: Historical research, analysis of documents found in the office of the director of the Nursing School, the directors of undergraduate and graduate nursing programs, publications, personnel archives of faculty members, interviews of retired faculty, and the authors´ recollections.Results: Four periods are depicted along the 65-year history, showing the development, achievements, and contributions of the academic programs and main extension projects; some challenges for the future also are included.Conclusions: Nursing-UniValle has been in the front line during its 65 years of history; now it has to meet the challenges of the future.